2022
DOI: 10.3390/ijms23158712
|View full text |Cite
|
Sign up to set email alerts
|

Burn-Induced Acute Kidney Injury–Two-Lane Road: From Molecular to Clinical Aspects

Abstract: Severe burn injuries lead to acute kidney injury (AKI) development, increasing the mortality risk up to 28–100%. In addition, there is an increase in hospitalization days and complications appearance. Various factors are responsible for acute or late AKI debut, like hypovolemia, important inflammatory response, excessive load of denatured proteins, sepsis, and severe organic dysfunction. The main measure to improve the prognosis of these patients is rapidly recognizing this condition and reversing the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 117 publications
1
11
0
Order By: Relevance
“…The above results suggest that skin inflammation might be connected to kidney inflammation, with the potential communication between inflammatory cells infiltrating the skin and the kidneys, in UVB-irradiated lupus-prone mice. In line, several studies have shown that neutrophils could be potential mediators of the link between skin inflammation and kidney injury in different scenarios, including skin thermal burn and UVB irradiation (33,34). Moreover, ours and other studies have reported the role of neutrophils and/or NETosis in UVBinduced skin inflammation (15,16) or lupus kidney inflammation (18,19) in mice.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…The above results suggest that skin inflammation might be connected to kidney inflammation, with the potential communication between inflammatory cells infiltrating the skin and the kidneys, in UVB-irradiated lupus-prone mice. In line, several studies have shown that neutrophils could be potential mediators of the link between skin inflammation and kidney injury in different scenarios, including skin thermal burn and UVB irradiation (33,34). Moreover, ours and other studies have reported the role of neutrophils and/or NETosis in UVBinduced skin inflammation (15,16) or lupus kidney inflammation (18,19) in mice.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, our results suggested a potential connection between skin inflammation and kidney injury in UVB-irradiated asymptomatic lupus-prone mice. Several recent studies have demonstrated the involvement of neutrophils in linking of skin inflammation to kidney injury, observed in different settings ( 3032 ). Previous studies from our team and others have shown the involvement of neutrophils and neutrophil NETosis in UVB-induced skin inflammation ( 15, 16 ) or lupus skin inflammation in the current study, and lupus nephritis ( 18, 19 ) in mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations